Elucidation of Biosynthetic Pathways of Natural Products. Issue 11 (7th April 2017) - Kishimoto, Shinji; Tsunematsu, Yuta; Sato, Michio; Watanabe, Kenji
Abstract: During the last decade, we have revealed biosynthetic pathways responsible for the formation of important and chemically complex natural products isolated from various organisms through genetic manipulation. Detailed in vivo and in vitro characterizations enabled elucidation of unexpected mechanisms of secondary metabolite biosynthesis. This personal account focuses on our recent efforts in identifying the genes responsible for the biosynthesis of spirotryprostatin, aspoquinolone, Sch 210972, pyranonigrin, fumagillin and pseurotin. We exploit heterologous reconstitution of biosynthetic pathways of interest in our study. In particular, extensive involvement of oxidation reactions is discussed. Heterologous hosts employed here are Saccharomyces cerevisiae, Aspergillus nidulans and A. niger that can also be used to prepare biosynthetic intermediates and product analogs by engineering the biosynthetic pathways using the knowledge obtained by detailed characterizations of the enzymes. (998 char.) Abstract : Biosynthetic pathways of fungal natural products having interesting chemical structures and valuable biological properties have been elucidated. Biosynthetic genes are identified through genome mining and genetic manipulation of the producing organism. Those genes are used for heterologous reconstitution of the biosynthetic pathway being studied in yeast or engineered fungi for preparing pathway products and intermediates. Lastly, detailed in vivo, in vitro and structural characterizations of the enzymes result in elucidation of unexpected mechanisms of secondary metabolite biosynthesis.